Pengaruh Disiplin Belajar Terhadap Prestasi Belajar Siswa - Al Milla Syifa Aulia; Supriyadi (Arden Jaya Publisher, 2022)
This study aims to reveal the effect of learning discipline (X) on learning achievement in social studies class VIII SMP Negeri 1 Setu (Y). This research uses quantitative research with a survey approach. The sample of this research used random sampling technique. The research population of class VIII students consisting of 11 classes, each class amounting to 35 so that the total number is 385 students, the research sample refers to Isaac and Michael's sample table for a population of 385 with a significance of 5% as many as 182. Data collection using valid and reliable instruments . Data analysis using simple regression. The results of the study revealed: (1) Linear Regression Equation Y = 65.288+0.458X (2) Learning discipline has a positive effect on student achievement. (3) The significance test obtained that the regression line equation F hit is smaller than 0.05 thus, Y or X regression is significant or learning discipline has an effect on learning achievement. (4) The correlation coefficient (rxy) = 0.665 and Fhit (Fchange) = 142.643, with a p-value less than 0.05. Thus, the correlation coefficients of X and Y are meaningful or significant. The coefficient of determination is 0.665, which means that 66.5% variation in learning achievement variables.